The Cα—H⋅⋅⋅O hydrogen bond: A determinant of stability and specificity in transmembrane helix interactions - Senes, Alessandro (The National Academy of Sciences, 2001)
The Cα—H⋅⋅⋅O hydrogen bond has been given little attention as a determinant of transmembrane helix association. Stimulated by recent calculations suggesting that such bonds can be much stronger than has been supposed, we have analyzed 11 known membrane protein structures and found that apparent carbon α hydrogen bonds cluster frequently at glycine-, serine-, and threonine-rich packing interfaces between transmembrane helices. Parallel right-handed helix–helix interactions appear to favor Cα—H⋅⋅⋅O bond formation. In particular, Cα—H⋅⋅⋅O interactions are frequent between helices having the structural motif of the glycophorin A dimer and the GxxxG pair. We suggest that Cα—H⋅⋅⋅O hydrogen bonds are important determinants of stability and, depending on packing, specificity in membrane protein folding.